UMP committed to continuous upgrading of community socioeconomic status - Zainal, Bahari (2019)
Universiti Malaysia Pahang (UMP) Advanced Education continues to play its pivotal role as the agent of change in bringing about a consistent upgrade of the socioeconomic status of the surrounding community, by offering various short-term programmes, including competency-building courses, in collaboration with both governmental bodies and the private sector.